2000
DOI: 10.1002/(sici)1521-3773(20000317)39:6<990::aid-anie990>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the Structure and Function of DNA: Insights into DNA Stability and Replication

Abstract: The physical and chemical factors that allow DNA to perform its functions in the cell have been studied for several decades. Recent advances in the synthesis and manipulation of DNA have allowed this field to move ahead especially rapidly during the past fifteen years. One of the most common chemical approaches to the study of interactions involving DNA has been the use of DNA base analogues in which functional groups are added, deleted, blocked, or rearranged. Here we describe a different strategy, in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
246
1
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 355 publications
(263 citation statements)
references
References 64 publications
(121 reference statements)
12
246
1
4
Order By: Relevance
“…This suggests that something other than the energetics of the newly-formed base pair accounts for the increased incorporation of dZTP opposite guanine, compared to dCTP. A similar behavior has been observed when other nucleoside analogs (35) and non-polar isosteres of nucleobases (36) were incorporated into DNA, indicating that the geometry rather than thermodynamic stability is important for DNA polymerase activity.…”
Section: Computer Modelingsupporting
confidence: 64%
“…This suggests that something other than the energetics of the newly-formed base pair accounts for the increased incorporation of dZTP opposite guanine, compared to dCTP. A similar behavior has been observed when other nucleoside analogs (35) and non-polar isosteres of nucleobases (36) were incorporated into DNA, indicating that the geometry rather than thermodynamic stability is important for DNA polymerase activity.…”
Section: Computer Modelingsupporting
confidence: 64%
“…41,42 The key step for these C-glycosides was glycoside bond formation (Scheme 2); in the presence of Pd(OAc) 2 and AsPh 3 , the iodinated base analogues were added via Heck reaction onto a silyl-protected dihydrofuran. 43 The syntheses of three yDNA nucleosides have also been reported recently.…”
Section: Synthesis Of Size-expanded Nucleosidesmentioning
confidence: 99%
“…6 Since hydrogen bonds are apparently dispensable in maintaining natural enzyme activity, we proposed that the fidelity of DNA replication might arise in large part from steric matching of bases within a tightly confined active site. 3,7,8 This hypothesis was criticized by suggesting that the reason that F behaved as such an effective mimic of T was that it actually did form robust hydrogen bonds with adenine.9 After this, several experiments and calculations with this fluorinated analogue and related compounds have concluded that C-F
H-N hydrogen bonding character is quite poor in this context, especially in the aqueous environment.10 -18 Nonetheless, a clearer way to avoid the issue of possible hydrogen bonds between F and A is to replace adenine with a nonpolar isostere, as was done for thymine. To this end, we chose a 4-methylbenzimidazole replacement used for adenine (Z) and studied its ability to be replicated opposite F. 19 , 20 It was found, interestingly, that this pair was an efficient substrate for the Klenow polymerase, and it was processed with significant levels of selectivity.…”
Section: Introductionmentioning
confidence: 99%